Detecting Plant Stress using Low-Cost Object Recognition Systems and Machine Learning Methods - S. Sureshkumar, V. S. Nishok, V. Jaikumar, Prasad Jones Christydass (Mathematical Statistician and Engineering Applications, 2021)
Agriculture is one of India’s primary economic pillars because so many people in the country work in it. Early identification of plant stress is a key advantage in intelligent agriculture. To improve the quality and productivity of food crops and to minimise plant damage, it is crucial to recognise plant stress using environmental indicators. Visual sensors in conjunction with environmental sensors help by spotting the leaf colour change early on, at which point further harm can be avoided. A trustworthy framework for identifying plant stress is proposed with the goal of making it easy for farmers to implement. The system uses a camera to take pictures of the leaves in the field, and then uses machine learning to determine if the leaves are healthy or not.